Information Day: Research Infrastructure Services in the Humanities and Social Sciences - Paneva-Marinova, Desislava; Goynov, Maxim; Luchev, Detelin; Zhelev, Yanislav; Monova-Zheleva, Mariya; Pavlov, Radoslav; Zlatkov, Lubomir; Noev, Nikolay; Pavlova, Lilia (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2022)
During the information day, the results of the work of the IMI-BAS team on the project CLaDA-BG, the Bulgarian National Interdisciplinary Research e-Infrastructure for Resources and Technologies in Favor of the Bulgarian Language and Cultural Heritage, Part of the EU Infrastructures CLARIN and DARIAH, will be presented: the development of the Humanities and Social Sciences Data Storage, Retrieval and Curation Environment (CHCS-DSRCE) and its implementation in the Digital Library "Virtual Encyclopedia of Bulgarian Iconography" and for the needs of the "Ivan Vazov" Regional Library in Plovdiv and “Peyo Yavorov” Regional Library - Burgas.